LDHA-mediated YAP lactylation promotes the tumor progression of hepatocellular carcinoma by inducing YAP dephosphorylation and activation - Xiaoyong Wei; Long Zou; Yanqing Huang; Chuan Qiu; Guang Cheng; Ye Chen; Jun Rao (Biology Direct)
Abstract Background Hepatocellular carcinoma (HCC) is among the deadliest cancers globally. Yes-Associated Protein (YAP), a Hippo pathway effector, crucially regulates cell proliferation and apoptosis. Recent research has implicated YAP’s role in HCC progression, but the mechanisms are unclear. This study aims to clarify YAP’s function in HCC, emphasizing its regulation of key pathways and targets. Results Gene knockout and overexpression models were established in nude mice and cell lines of HCC cells to investigate YAP’s impact on tumorigenesis. Additionally, functional assays and molecular biology techniques were employed to identify YAP’s regulatory networks. The study demonstrates that LDHA-regulated lactate production promotes YAP activation and malignant phenotypes in HCC. Overexpression of LDHA in HepG2 and Huh7 cells increased lactate levels and activated the YAP pathway, enhancing cell proliferation, migration, and invasion. Lactate treatment also promoted these malignant phenotypes by inhibiting YAP phosphorylation at Ser127. In a xenograft model, lactate accelerated tumor growth through YAP activation. YAP lactylation at K102 antagonized its Ser127 phosphorylation, further promoting malignant progression. Conclusions This study highlights the significance of YAP in HCC pathogenesis, providing insights into potential therapeutic targets for HCC management. Graphical Abstract